Activity of Silver Nanoparticles Synthesized From Buttermilk Filtrate and Activity of Spices against Dental Cavity Causing Organisms - Memane, Prasad; Patil, Smita; Sarje, Ashwini (International Journal of Scientific Research in Biological Sciences, 2021)
Bacterial oral pathogens can cause severe diseases with complications, severe soft tissue invasions, toxic syndromes and also cause infective endocarditis. This research paper provides comprehensive view on the silver nanoparticle synthesis from buttermilk filtrate, its characterization and its antimicrobial activity against dental pathogens. Also some spices was used to check their antimicrobial potential. The dental cavity causing organisms were isolated from patients having dental cavity problems. These organisms were identified as streptococcus spp. and candida spp. by performing morphological, cultural and biochemical characteristics referring to the bergey’s manual of determinative bacteriology. Silver nanoparticles were synthesized using buttermilk filtrate and characterization were done by UV-Vis spectroscopy and scanning electron microscopy. Extract of different spices as well as biologically synthesized silver nanoparticles were checked against identified clinical isolates by well diffusion method. Nanoparticles synthesized using buttermilk filtrate were more effective as compared to crude extracts against pathogenic strains of bacteria.